The Changes of Peat Chemical Characteristics which is Converted from Oil Palm to Corn Plantation Areas In Kinali, West Pasaman Regency, West Sumatra - Harianti, Mimien; Prasetyo, Teguh Budi; Junaidi, Junaidi; Naspendra, Zuldadan; Batara, Dewi Syaputri (LPPM Universitas Andalas, 2022)
The decline in production prices and land ownership shifts have caused people to choose to convert oil palm plantations into corn plantations. Changes in land cover from plantation crops to annual crops is potentially to reduce the chemical properties of peat. This study aims to identify changes in the chemical properties of peat on land for conversion of oil palm to corn plantations. This research was carried out from May to September 2021. Observations and peat sampling were carried out using the Transect method, perpendicular from the drainage channel based on a distance of 2m, 200m, and 400m from the main canal in maize conversion age < 2 years, (3) maize planting aged conversion 2 years. For each land use, 3 sample points were taken with 2 replications at a depth of 0-20 cm and 20-40 cm. The chemical properties of peatlands that have been converted from oil palm plantations to corn plantations include pH 4.18-4.98, water content 163.76-495.81%, ash content 15.5-72.12%, C-Organic 16.18-49.02%, N-Total 1.25-6.92%, P-Total 5.56-255.87 ppm, P-Available 0.63-157.43 ppm, K-dd 0, 38-1.98 me/100g, Na-dd 3.97-13.84 me/100g, Ca-dd 12.26-23.12 me/100g, Mg-dd 14.66-50.84 me/100g , CEC 63.30-498.16 me/100g, total acidity 570-600 cmol/kg-1. After land conversion, the quality of peatlands increased, especially at the age of conversion <2 years and decreased with increasing age of land conversion.